Demographic profile of COVID-19 patients in the Northern part of Bangladesh - Zahid, M. Abu; Uddin, M. Bashir; Islam, Mazharul (International Journal of Advances in Medicine, 2022)
Background: It is a new pandemic; the demographic profile of COVID-19 patients may be helpful for corona virus patients. Methods: This was a cross-sectional study conducted at the department of cardiology at Rangpur medical college hospital, Rangpur, Bangladesh during July 2020 to December 2020. In total 37 confirmed COVID-19 patients were selected as the study population. Data were collected from patients or their attendants by using a pre-designed structured questionnaire, after having appropriate consent. The statistical package for the Social sciences (SPSS) version 22.0 was used for data analysis. Results: In this study 70% participants were male whereas 30% were female and the ratio was 2.36:1. The mean±SD age of the participants was 56.57±15.96 years. The highest number of participants were from 51-60 years’ age group which was 27.3%, 2.70%, 18.92%, 16.22%, 13.51%, and 21.62% participants were from 21-30, 31-40, 41-50, 61-70 and >70 years of age group respectively. The majority portion of participants were with normal body-weight (BMI: 18.5-24.9) which was in 57% and 43% were with overweight (BMI: 25.0-29.9). More than half of the patients were from Rangpur district which was 54%. The highest number of patients were with cough as a major symptom, which was 51.35%. The highest number of participants were with IHD (64.86%) as a major comorbidity. Conclusions: As per the findings of this study, we can conclude that, middle aged population are mostly being affected by COVID-19 in Bangladesh. The affected number of males were higher than female.